Case study: Use of contact lenses to manage complications following combined corneal cross-linking and topography-guided photorefractive keratectomy for pellucid marginal degeneration - Yeung, D; Sorbara, Luigina (Canadian Journal of Optometry, 2016)
This case report describes two significant long-term complications experienced by a patient following treatment for pellucid marginal degeneration (PMD). Two years after undergoing a combination of topography-guided photorefractive keratectomy (T-PRK) and corneal collagen cross-linking (CXL) procedures, the patient continued to experience glare and dryness associated with persistent stromal haze and dry eye. These procedures resulted in dissatisfaction with the final outcome, which led the patient to seek contact lens correction. Management of the symptomatic ocular sequelae with specialty soft toric contact lenses designed for irregular corneas supported her visual rehabilitation.